The Self-Healing Capability of Carbon Fibre Composite Structures Subjected to Hypervelocity Impacts Simulating Orbital Space Debris. (30th December 2012) - Aïssa, B.; Tagziria, K.; Haddad, E.; Jamroz, W.; Loiseau, J.; Higgins, A.; Asgar-Khan, M.; Hoa, S. V.; Merle, P. G.; Therriault, D.; Rosei, F.
Abstract : The presence in the space of micrometeoroids and orbital debris, particularly in the lower earth orbit, presents a continuous hazard to orbiting satellites, spacecrafts, and the international space station. Space debris includes all nonfunctional, man-made objects and fragments. As the population of debris continues to grow, the probability of collisions that could lead to potential damage will consequently increase. This work addresses a short review of the space debris "challenge" and reports on our recent results obtained on the application of self-healing composite materials on impacted composite structures used in space. Self healing materials were blends of microcapsules containing mainly various combinations of a 5-ethylidene-2-norbornene (5E2N) and dicyclopentadiene (DCPD) monomers, reacted with ruthenium Grubbs' catalyst. The self healing materials were then mixed with a resin epoxy and single-walled carbon nanotubes (SWNTs) using vacuum centrifuging technique. The obtained nanocomposites were infused into the layers of woven carbon fibers reinforced polymer (CFRP). The CFRP specimens were then subjected to hypervelocity impact conditions—prevailing in the space environment—using a home-made implosion-driven hypervelocity launcher. The different self-healing capabilities were determined and the SWNT contribution was discussed with respect to the experimental parameters.